5(2q)+(q-4)+q=5

Simple and best practice solution for 5(2q)+(q-4)+q=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2q)+(q-4)+q=5 equation:


Simplifying
5(2q) + (q + -4) + q = 5

Remove parenthesis around (2q)
5 * 2q + (q + -4) + q = 5

Multiply 5 * 2
10q + (q + -4) + q = 5

Reorder the terms:
10q + (-4 + q) + q = 5

Remove parenthesis around (-4 + q)
10q + -4 + q + q = 5

Reorder the terms:
-4 + 10q + q + q = 5

Combine like terms: 10q + q = 11q
-4 + 11q + q = 5

Combine like terms: 11q + q = 12q
-4 + 12q = 5

Solving
-4 + 12q = 5

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 12q = 5 + 4

Combine like terms: -4 + 4 = 0
0 + 12q = 5 + 4
12q = 5 + 4

Combine like terms: 5 + 4 = 9
12q = 9

Divide each side by '12'.
q = 0.75

Simplifying
q = 0.75

See similar equations:

| 9x+5y+0.1z=100 | | 2(6)(h)+2(h)(17)+2(6)(17)=342 | | 6x=x+6 | | 2(6)(h)+2(h)(17)+2(6)(17)=h | | 12.5y+30+130-30=180 | | 13x-30=100 | | 9r=81 | | (2k+1)(2m+1)= | | -2-ln(x+1)=0 | | 20x^2-2x-4=0 | | 72x^2+96x-936=0 | | 4x+-6=34 | | -2x-(-8+3x)=6 | | y=-3x+-8 | | 3x+12-7*3x=123 | | (y+7)(y-8)= | | 72x^2-2496x-936=0 | | 98-7(10)= | | 98-7(-5)= | | (8x+1)-(-5x+5)= | | 98-7(280)= | | 2x^2-18x+45=0 | | y=5E-06x+0.24 | | 11=18-x | | (7x+5)+(-8x+6)= | | 0.29=logx | | x=log(3)(48) | | 3/4t-6=1/3t-1 | | 3/2t-6=1/3t-1 | | nx+b=6(x-n)forx | | nx+b=6(x-n) | | 3x(x+4)=3(x-1) |

Equations solver categories